Assessing the Family Centered Maternity Care Practices of a Community Health Center in Chhattisgarh, India - Samal, Dr. Janmejaya (Asian Journal of Pharmaceutics (AJP), 2016)
Background: Albeit family centered maternity care is hardly being practiced in public health institutions in India; however, it can contribute in a better way to maternity care and help improve many of the maternal health indicators. Objective: The primary objective of this study was to assess the family centered maternity care practices of a community health center. Methodology: To assess the family centered approach (FCA) three different modalities were adopted; in-depth interview with a nursing staff, observation and record review. Results: It was observed that the community health center is managed by a nongovernmental organization and FCA is partially being observed in its approach to maternity care. It was observed that the nursing staff was able to evoke client participation among all the five pregnant women (as observed during conversation) however she was not respectful to the clients and her active listening skills were partial and was partially compassionate. Similarly, when the participatory approach of the nursing staff was assessed it was found that the nurse could develop a collaborative approach with all the five pregnant women however she could partially able to develop client autonomy and was partially responsive and partially allowed the clients to have their own choice. Conclusion: Practice of FCA can yield better maternal health outcomes and help improve the maternal health indicators